Kandungan Pewarna Rhodamin B Pada Saus Sambal Dalam Kemasan yang Beredar di Pasar Tradisional Rawasari Cempaka Putih dan Tinjauannya Menurut Pandangan Islam - Salsabila, Dindana Caesarea; Suciati, Yulia; Suseno, Dedy; Roswiem, Anna P.; Qomariyah, Qomariyah; Arsyad, Muhammad (Publikasi Indonesia, 2022)
The content of harmful dyes such as Rhodamine B in food, especially chili sauce in packaging, can be dangerous. The purpose of this study was to determine and identify the presence or absence of synthetic dye Rhodamin B in packaged chili sauce circulating in the Rawasari Cempaka Putih Traditional Market. This research is an experimental research, namely by conducting qualitative laboratory tests with thin layer chromatography and quantitative with UV-vis spectrophotometer to analyze the presence of Rhodamine B in packaged chili sauce sold in the traditional market of Rawasari Cempaka Putih. The samples used in this study were all types of packaged chili sauce which had striking red color characteristics and were taken randomly from the survey results at the Rawasari Cempaka Putih traditional market with a random sampling determination of the sample. The results showed that the five samples of packaged chili sauce sold at Pasar Rawasari Cempaka Putih had final results which stated that Rhodamine B dye was not detected.